Pengaruh Nilai Tukar dan Kebijakan Moneter The Federal Reserve terhadap Return Saham Volkswagen AG: (Studi Kasus pada Perusahaan Multinasional) - Rendra Dwi Saputra; Muhammad Faizal Hakim; Saddam Abhinaya Setiyawan; Aldan Ardana; Chetrine Alya Rinaima (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to analyze the impact of the USD/CNY exchange rate and the Federal Reserve interest rate on the stock returns of Volkswagen AG. Volkswagen AG is chosen as the object of analysis because it is a multinational corporation with significant exposure to the Chinese market, making it highly sensitive to fluctuations in global economic conditions, particularly exchange rate movements and monetary policy changes. The study adopts a quantitative research approach using multiple linear regression analysis to examine the relationships between variables. The data used are monthly secondary data covering the period from 2017 to 2023, resulting in 84 observations. The dependent variable in this study is Volkswagen AG stock returns, while the independent variables consist of the USD/CNY exchange rate and the Federal Funds Rate. The empirical results show that the USD/CNY exchange rate has a negative and statistically significant effect on Volkswagen AG stock returns, indicating that currency depreciation or appreciation plays a crucial role in influencing investor sentiment and firm valuation. In contrast, the Federal Funds Rate does not show a statistically significant effect on stock returns during the observed period. However, the simultaneous test indicates that both variables jointly have a significant influence on Volkswagen AG stock returns. Overall, the findings suggest that exchange rate risk is more dominant than U.S. monetary policy in affecting the stock performance of Volkswagen AG over the study period.